An Experimental Method of Determining Explosive Equivalency When Scaled Distance Approaches Zero - R. Alford; R. Hazael; R. Critchley (International Society of Explosives Engineers, 2024)
The ability to compare explosives is fundamental. Numerous methods are used and while simple conversion factors are often used, the use of TNT Equivalency (TNTe) is not a simple subject as explosives exhibit very different equivalencies depending on whether the pressure or impulse are being considered as well as other conditions. The scaled distance has been found to have a significant effect on the TNTe but due to the difficulty of taking measurements at very close ranges, no TNTe have been quoted for charges in direct contact (Z=0). This paper describes the use of a ballistic pendulum to measure the impulse from contact charges and presents some surprising results that require a two-stage propulsion, as originally described by Backofen, to be explained.